BIOLOGICAL ACTIVITY OF HYPERICUM PERFORATUM L. (HYPERICACEAE): A REVIEW - A. L. Budantsev; V. A. Prikhodko; I. V. Varganova; S. V. Okovityi (Фармация и фармакология (Пятигорск))
Hypericum perforatum L. (St. John's wort) is a medicinal plant that has been intensivly studied by clinicians, pharmacologists, and chemists. It has resulted in the publication of both original articles and a number of, reviews devoted to the general spectrum of the biological activity of its extracts and the separate chemical components of this species. Unlike many other known medicinal plants, the pharmacological study of which is accompanied by the establishment of new (or rediscovered) structures of chemical compounds, the dynamics of the present study of H. perforatum is mostly associated with a detailed study of the mechanisms of its therapeutic effect and less with the search for new components.The aim of this work is to review and analyze the data on the biological activity of extracts and individual components of Hypericum perforatum L. (Hypericaceae), or St. John's wort, published in the scientific literature over the past 10 years.Materials and methods. To collect and analyze the information, such electronic databases as PubMed, Scopus, Web of Science, Google Scholar, and other available resources have been used. The following keywords and word combinations were used for search in the databases for 2010-2020: “Hypericum perforatum”, “St. John's wort”, “the biological activity of St. John's wort”, “hypericin”, “hyperforin”.Results. The review provides information on antidepressant, neuroprotective, nootropic, anxiolytic activity, antibacterial, cytotoxic, anti-inflammatory properties, analgesic, hypoglycaemic effects, and other types of activity of H. perforatum extracts, as well as individual compounds (hypericin, hyperforin, amentoflavone, and others), isolated from this species. It is well known that the secondary metabolites of St. John's wort are naphthodianthrons, flavonoids and other phenolic compounds, several classes of lipophilic substances including phloroglucinol derivatives and terpenoids. Apart from extracts and their fractions, the biological activity of photoreactive naphthodianthrone hypericin and hyperforin (a phloroglucinol derivative) has been studied in detail.This review provides an analysis of published data from 2010 to 2020 on the biological activity of St. John's wort. At the present time H. perforatum is primarily well-known for its antidepressant-like properties, which are confirmed by numerous pharmacological studies and clinical trials. Still there is no consensus on the effective treatment of severe or even moderate depression with St. John's wort. This review also provides information on the neuroprotective, nootropic, antiepileptic, anxiolytic, antimicrobial, antiviral, antiprotozoal, antitumor, cytotoxic, analgesic, anti-inflammatory and other effects of H. perforatum extracts, as well as its individual compounds.Conclusion. Despite the popularity of H. perforatum as a plant with an antidepressant-like activity, intensive research work continues to be carried out to elucidate the molecular mechanisms of the actions of extracts and individual compounds in disorders of the nervous system. Studying its antibacterial, antiviral, and cytotoxic activity may also open up some great prospects, along with determining the possibility of using St. John's wort in metabolic disorders, genitourinary disorders, and other fields of medicine.